2017
DOI: 10.5535/arm.2017.41.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Selective Focal Ablation by Navigable Percutaneous Disc Decompression Device in Patients With Cervical Herniated Nucleus Pulposus

Abstract: Objective To evaluate the clinical efficacy and safety following percutaneous disc decompression, using navigable disc decompression device for cervical herniated nucleus pulposus (HNP). Methods Twenty subjects diagnosed with cervical HNP and refractory to conservative management were enrolled for the study. The herniated discs were decompressed under fluoroscopic guidance, using radiofrequency ablation device with navigable wand. The sagittal and axial plain magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…There are some nonsurgical interventions for the treatment of CDH that usually aim to directly cauterize the discal parts, making use of various devices that approach anteriorly to the cervical disc (11,12). There is a need for comparative studies analyzing the results and long-term effects of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…There are some nonsurgical interventions for the treatment of CDH that usually aim to directly cauterize the discal parts, making use of various devices that approach anteriorly to the cervical disc (11,12). There is a need for comparative studies analyzing the results and long-term effects of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of intra discal electrothermal therapy (IDET) is generally used to describe the methods used to achieve the thermal ablation of the intervertebral discs. This thermal ablation can be achieved with radiofrequency waves or laser energy (1,9). While naming the prosedure, the names "percutaneous disc coagulation" (PDC), "anuloplasty", and "nucleoplasty" are far from explaining what kind of energy ablation is used.…”
Section: Discussionmentioning
confidence: 99%
“…When this theory did not find much support, new devices have been developed which aiming to coagulate anulus fibrosus (AF) rather than nucleus pulposus, considering that the pain is actually due to degenerated AF. Thus, the systems that are contacting the inner surface of the AF by using guidable catheters and thus coagulating a larger AF region were developed (4,5,9). But in recent studies, contrary to the previously known, it has been shown that there are newly sprouted nerve endings into the degenerated nucleus pulposus (NP) due to degenerative processes, and these new nerve endings may be responsible for discogenic pain (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al ( 20 ) evaluated data of patients with both radicular and axial pain ( 18 ) and with discogenic waist pain ( 21 ) who had lumbar disc decompression performed using L’DISQ TM . Kim et al ( 22 ) studied patients with cervical herniated nucleus pulposus who were resistant to prior treatments. They concluded that the technique was effective in the cervical region as well as the lumbar region.…”
Section: Discussionmentioning
confidence: 99%